Hypoxic acclimatization training improves the resistance to motion sickness - Wang, Rui; Yan, Yiquan; Tie, Yateng; Zhang, Qi; Pan, Yikai; Li, Shuhan; Fan, Jieyi; Li, Chengfei; Li, Xi; Wang, Yongchun; Sun, Xiqing; Zhang, Tongmei; et al. (Frontiers in Neuroscience, 2023)
Objective Vestibular provocation is one of the main causes of flight illusions, and its occurrence is closely related to the susceptibility of motion sickness (MS). However, existing training programs have limited effect in improving the resistance to motion sickness. In this study, we investigated the effects of hypoxia acclimatization training (HAT) on the resistance to motion sickness. Methods Healthy military college students were identified as subjects according to the criteria. MS model was induced by a rotary chair. Experimental groups included control, HAT, 3D roller training (3DRT), and combined training. Results The Graybiel scores were decreased in the HAT group and the 3DRT group and further decreased in the combined training group in MS induced by the rotary chair. Participants had a significant increase in blood pressure after the rotary chair test and a significant increase in the heart rate during the rotary chair test, but these changes disappeared in all three training groups. Additionally, LFn was increased, HFn was decreased, and LF/HF was increased accordingly during the rotary chair test in the control group, but the changes of these three parameters were completely opposite in the three training groups during the rotary chair test. Compared with the control group, the decreasing changes in pupillary contraction velocity (PCV) and pupillary minimum diameter (PMD) of the three training groups were smaller. In particular, the binocular PCV changes were further attenuated in the combined training group. Conclusion Our research provides a possible candidate solution for training military pilots in the resistance to motion sickness.